The Iatrogenic Perspective on Contemporary Legends: Analysisof the Basque Case - Rodriguez, Fito (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2012)
The contemporary rumours and legends are an oral tool for transmitting information with sensitive content. They work like "social analyzers", they are informing us in a profound way about the sociologic situation and about the hidden wishes of society. In this article we are analyzing both of those aspects by creating situations in the case of urban and contemporary rumours and legends in the Basque country